A new dinosaur tracksite with small footprints in the Urbión Group (Cameros Basin, Lower Cretaceous, La Rioja, Spain) - Díaz-Martínez, I.; García-Ortiz, E.; Pérez-Lorente, F. (Journal of Iberian Geology, 2015)
A new dinosaur tracksite (La Rueda) with ten small tridactyl footprints (the length ranges between 9 and 15 cm) from the Urbión Group (Cameros Basin, Lower Cretaceous, La Rioja, Spain) is described. The footprints are approximately as long as wide and have high divarication angles between digits II-IV ( 80º), some pad impressions on each digit, claw marks, a medial notch and a circular heel pad impression. They are here classified as indeterminate ornithopod footprints and contribute to the increase in the dinosaur ichnodiversity of the Urbión Group. Small dinosaur footprints are scarce in the worldwide fossil record. In the Urbión Group, large dinosaur tracks are much more frequent than small ones. This scarcity could be explained as ecological biases (dearth of small individuals in an area). Nevertheless, the number of small footprints in the Urbión Group is instead the product of by preservation biases (coarse grain sediments and fluvial erosive bases) and the weathering and erosion processes (brittle nature of the rock) that affect especially to small tracks than large ones identified in this Group.